Analysis of an electrochemical compressor stack. (13th November 2020) - Chouhan, Ashish; Aryal, Utsav Raj; Bahar, Bamdad; Prasad, Ajay K.
Abstract: Electrochemical compression (ECC) of gases offers advantages over conventional mechanical compression such as higher efficiency and noiseless operation. However, ECC performance can be affected by back-diffusion of the gas across the membrane which is exacerbated at high pressures. Practical systems employ multiple cells in a stack configuration to achieve higher flowrates and gas pressures. Here, we analyze two different stack configurations in order to understand their influence on gas throughput and exit pressure in the presence of back-diffusion. Both the stack configurations examined here are connected electrically in series such that the external voltage applied to the stack terminals is divided equally across each individual cell. On the other hand, the flow of gas within the stack can occur either in parallel or in series. Accordingly, we name these stack configurations Electrically in Series/Flow in Parallel (ESFP), and Electrically in Series/Flow in Series (ESFS). The ESFP configuration can deliver higher gas throughput but at limited pressures, whereas the ESFS configuration can deliver higher pressures but at lower flowrates. A theoretical performance analysis has been conducted for both configurations to gain insights into the compressed gas flux, pressure rise, back diffusion, and efficiency. Furthermore, it is also possible to design a hybrid configuration that combines both parallel and series flow aspects to deliver flow and pressure that is optimized for a given application. Highlights: Electrochemical compressors can be more efficient than conventional compressors. Two types of electrochemical compressors are proposed: ESFP and ESFS. Compressed gas flux, pressure rise, back diffusion, and efficiency are analyzed. A third hybrid configuration is proposed that combines features of ESFP and ESFS.